Evaluation of toxic effects of Coleus forskohlii extract on various body organs of experimental animals-rats - Haritha Yadav KC; Yakaiah Vangoori; Suresh Babu Sayana (Asian Journal of Medical Sciences, 2022)
Background: The study aimed observation of pharmacological actions and any adverse effects on various body organs of rats with Coleus forskohlii (CF) extract. Aims and Objectives: The present study was undertaken to evaluate toxic effects of CF extract in experiments animals. Materials and Methods: In the single-dose oral toxicity study, groups of five healthy male and female rats were dosed orally with CF extract at 2000mg/kg BW as per organization of economic cooperation and development guidelines and were observed once daily for 14 consecutive days for toxicity, general behavior, and pharmacological effects. In sub-acute oral toxicity, the test substance was administered for 28 days with daily doses of 200, 400, and 800 mg/kg body weight. In subacute oral toxicity study, groups of five male and five female rats were subjected to 10% forskolin for 28 days. Initially autonomic symptoms (gross behavioral study), followed by hematological, biochemical, and histological parameters, were evaluated. Results: No deaths were reported in all the toxicity studies performed. No significant changes were observed in the hematology and serum biochemistry values from the control group animals. The body weight changes and necropsy results were normal. There was no apparent progression of organ damage in any of these toxicity tests. Furthermore, CF extract did not produce any significant toxic effects in Wistar rats at 2000 mg/kg body weight and had no potential to induce organ damage. Conclusion: The “no observed adverse effect level” of CF extract was determined up to 2000 mg/kg.